How does Pancasila work in countering radicalism and terrorism in Indonesia? - Ariyani, Sri Dewi (Jurnal Scientia Indonesia, 2016)
Pancasila is a solution to the problems of radicalism that have hit Indonesia today. Then it is hoped that the values in Pancasila must be truly carried out by the Indonesian people to prevent and minimize radicalism and terrorism in our beloved country. The loss of values contained in Pancasila in Indonesian society is the basis of the emergence of various acts of radicalism terrorism in Indonesia. Therefore, the implementation of Pancasila values, in order to remain current in the face of the threat of radicalism must be emphasized in the delivery of the following three messages: 1. This country is formed based on agreement and equality, in which no one should feel as a major shareholder, or first class citizen. 2. Rules for playing in a state have been agreed upon, and the State has full sovereignty to bring order to the members of its country who try systematically to change the order, in ways that are against the law. 3. The state provides protection, opportunity, future and balanced protection to achieve the national goals of a just and prosperous society, prosperous, safe, civilized and free.           The Indonesian government recently began to be aware of the development of radicalism in the country related to the ISIS network (the Islamic State of Iraq and Syria). This issue about ISIS has become a global issue and it seems the world is compact to fight it. Seeing this phenomenon, there needs to be steps to prevent acts of radicalism from flourishing on the earth. In addition to taking action on radicalism, the government must also prevent or preventive measures so that people are not easily provoked against ideologies that use religious attributes. Close collaboration between the government, security forces and religious leaders is needed to rectify religious understanding.